Quality Assessment of the Clinical Practice Guidelines of Ostomy Care Based on the AGREE II Instrument - Li, Xiaoyu; Yuan, Qiao; Geng, Liangrong; Chen, Zhiqi; Zhang, Rui; Guo, Liqun; Yue, Shujin (Frontiers in Public Health, 2022)
Objectives: To assess the quality of clinical practice guidelines (CPGs) of ostomy care, and to analyze the status quo and challenges of guideline development. Methods: CPGs of ostomy care were systematically searched in relevant guideline websites and electronic databases, including PubMed, ProQuest, Web of Science, CNKI, VIP, WANFANG, and SinoMed, from January 1, 2012, to November 24, 2021. Two appraisers used the Appraisal of Guidelines for Research and Evaluation, 2nd edition (AGREE II) instrument to assess the quality of the included CPGs independently and objectively. The consistency of assessment was calculated using intraclass correlation coefficients (ICC). Results: A total of 5 CPGs relevant to ostomy care were assessed by AGREE II and the general quality of them was good. There were two CPGs of grade A and three CPGs of grade B. The domain scope and purpose (87.78%) had the highest scores, followed by the clarity of presentation (87.22%), the rigor of development (69.17%), stakeholder involvement (68.33%), and editorial independence (65.00%), and the lowest was applicability (55.42%). The overall assessment score was 5.40. All the ICCs for the AGREE II appraisal conducted by the two appraisers were greater than 0.75. Conclusions: The five CPGs of ostomy care have the potential to be adopted in clinical practice. However, they still have some room for improvement, especially in the applicability domain. The development of ostomy care CPGs should follow the evidence-based progress and methodology of guideline formulation specifications while considering the effects of the CPGs and the practical issues.